A case of severe hypoglycemia after gastric bypass surgery in a woman with non-alcoholic fatty liver disease (NAFLD) - GONZALO (2022)
Post-gastric bypass hypoglycemia is characterized by postprandial hypoglycemia with pancreatic islet-cell hypertrophy in patients who have undergone a bariatric surgery and may be prone to hypoglycemia due to NAFLD, obesity, and impaired insulin and glucagon secretion.We present the case of a 44-year-old obese woman with NAFLD who underwent a Roux-en-Y gastric bypass and years later presented with severe hypoglycemia. She was diagnosed with endogenous hyperinsulinemic hypoglycemia and beta-cell hyperplasia.Post-gastric bypass hypoglycemia is a scenario that will be faced more often; therefore, it is important to take it into account for a timely treatment.